ARTFUL NAIVETE. NOTES ON THE POETRY COLLECTIONS MEZI NAMA AND BETONOVA PLAZ BY SIMON LEITGEB - Lukas, Martin (Bohemica Olomucensia, 2023)
Promising Czech poet Simon Leitgeb (born 1996) has received rather favourable reviews of his two poetry collections published so far, i.e., Mezi nama (Among Us, 2017) and Betonova plaz (The Cement Beach, 2020), the second of which Leitgeb was given the Jiri Orten Award for, a Czech literary prize for young authors under the age of 30. Almost all of the reviewers recognized ``naivete'' as a constitutional quality of Leitgeb's poetry. However, too few of them saw this ``naivete'' as part of the author's cunning stylization, or an artful means of arousing readers' sympathy for or bringing their attention to the characters and situations as depicted in the poems by the fictional speaker, himself being ``naive'' in particular.
Keywords: Simon Leitgeb; Mezi nama; Betonova plaz; Czech poetry; naivete; fictional speaker